Role of particle size and surface functionalisation on the flexibility behaviour of switchable metal–organic framework DUT-8(Ni). Issue 43 (28th October 2020) - Thompson, Megan J.; Hobday, Claire L.; Senkovska, Irena; Bon, Volodymyr; Ehrling, Sebastian; Maliuta, Mariia; Kaskel, Stefan; Düren, Tina
Abstract : Functionalising the external surface of flexible MOF nanoparticles allows manipulating the gate opening/closing pressure. Abstract : Flexible MOF nanoparticles, i.e. MOF nanoparticles that change their structure upon external stimuli such as guest uptake, are promising for numerous applications including advanced gas adsorption, drug delivery and sensory devices. However, the properties of MOFs are typically characterised based on the bulk material with no consideration of how the particle size and external surface influences their performance. This combined computational and experimental contribution investigates the influence of the particle size and surface functionalisation on the flexibility of DUT-8(Ni) (Ni2 (2, 6-ndc)2 dabco, ndc = naphthalene dicarboxylate, dabco = 1, 4-diazabicyclo[2.2.2]octane, DUT = Dresden University of Technology). DUT-8 nanoparticles remain rigid in their open pore form while microparticles, synthesised under slightly different conditions, undergo gate opening upon nitrogen adsorption suggesting that the particle size has an important role to play in the flexibility of DUT-8. While the adsorption environment at the surface capped with modulators smaller than the 2, 6-ndc ligand is very different compared to the bulk of the crystal with considerably weaker guest–framework interaction, simulations reveal that the nanoparticles should close. We conclude that the size of the nanoparticles is not the major contributor for keeping DUT-8 nanoparticles open but that it is more likely that defects or nucleation barriers dominate. Moreover, our work reveals for the first time that functionalising the external surface of nanoparticles with different modulators or capping groups offers the opportunity to manipulate the gate opening/closing pressure. This principle is generally applicable and could be exploited to tune the gate opening/closing pressure for the application of interest.